Implementasi Pengelolaan Barang Milik Negara dalam Menjaga Kesesuaian Data Administrasi: Studi pada BPK Perwakilan Provinsi Bali - Ni Putu Herdina Divya Aristyarani; I Kadek Rian Prayana (MASALIQ, 2026)
The management of Barang Milik Negara (BMN) plays a crucial role in ensuring accountability and optimization of government assets; however, in practice, various challenges are still encountered, particularly regarding the accuracy of administrative data, the alignment between physical asset conditions and records, and the effectiveness of information system usage. This study aimed to examine the implementation of BMN management at BPK Perwakilan Provinsi Bali and to analyze the factors influencing the effectiveness of asset administration based on Edward III’s policy implementation model, which comprises the dimensions of communication, resources, disposition, and bureaucratic structure. A descriptive qualitative method was employed through interviews, observation, and document study involving officials responsible for BMN management. The findings show that BMN management has essentially followed established procedures, yet still faces obstacles such as limited human resources, suboptimal internal socialization, differing understandings of asset classification, and technical constraints in the SIMAN V2 application, including unstable internet connectivity and inefficient barcode scanning. These results underscore that the effectiveness of BMN management is strongly influenced by the quality of communication and coordination, improvement of managers’ competencies, upgrading of technological infrastructure, and strengthened periodic physical verification of assets, all of which constitute critical prerequisites for achieving accountable and optimal state asset administration.